VARIAÇÃO FENOTÍPICA EM RESPOSTA À SAZONALIDADE ALIMENTAR EM Drosophila mojavensis sonorensis (DIPTERA: DROSOPHILIDAE) - Prestes, Jaqueline de Oliveira (2017)
Many insects are saprophytophagous and use host plants during their life cycle. Among these are the flies of the Drosophila genus (Diptera: Drosophilidae). Changing host requires the flies to have adaptation ability to new biotic factors. The cactophilic subespecies Drosophila mojavensis sonorensis belongs to the repleta group, inhabits the Sonora Desert and participates in the cactus - yeast - Drosophila system. Usually it uses roting cladodes of the columnar cactus Stenocereus thurberi, but recently these flies were also detected using decomposing fruits of Opuntia spp. as alternative seasonal host. These two hosts have several differences regarding their chemistry, spatial distribution and the time interval in which the decomposing tissues are suitable for use, which can cause stress to the development of the flies. Therefore, the objective of this study was to verify, through the geometric morphometry, the effects of the use of the different hosts on morphological structures sensitive to environmental changes, the wings and the aedeagus, in D. m. sonorensis sampled at three locations in the Sonora Desert in Mexico. For this, 2nd instar larvae were seeded in semi-natural diets containing or cladodes of S. thurberi or fruits of Opuntia spp. The adults obtained were placed in ethanol and stored at 20°C for later wings and aedeagus removal, which were used in the morphometric analyzes. Morphometric analyzes of the wings were performed using two approaches: 1) comparing the levels of asymmetry between the diets and localities to measure larval stress level; and 2) analyzing wing shape and size. The aedeagi were analyzed regarding morphometric alterations in shape and size. Among the results, it was verified the occurrence of phenotypic variation of the wings and the aedeagus, both among populations and between diets. Each population showed to have a specific genetic pool and responded differently when subjected to the diets. The wings presented asymmetric deviation, with fluctuating and directional asymmetry in males and females, demonstrating that there is stress in larval development in both diets, probably caused by specific chemical compounds of each host, allelochemicals in cladodes and sugars in tunas. Populations with similar responses to the same environmental pressures showed a phenotypic proximity. The ability of these organisms to explore two different hosts can be an advantage, increasing the niche and reducing intra and interspecific competitiveness. So, the morphological changes, caused by the environmental stress detected in this study, may lead to changes in the biology, ecology and evolution of these organisms. Therefore, further studies investigating the chemical composition of different hosts, and the influence of each host on the organism of the insects are important for biological and evolutionary studies.